2016
DOI: 10.1007/s10035-016-0660-y
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element simulation of railway ballast: modelling cell pressure effects in triaxial tests

Abstract: The paper investigates reproducing the effects of confining pressure on the behaviour of scaled railway ballast in triaxial tests in discrete element models (DEM). Previous DEM work, using a standard Hertzian elastic contact law with an elastic-perfectly plastic tangential slip model, has been unable to replicate the behaviour observed in laboratory tests across a range of confining pressures without altering both the material stiffness and the inter-particle friction. A new contact law modelling damage at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 23 publications
4
67
1
Order By: Relevance
“…This turned out to be impossible (at least for the used simple clump shape), as in the Hertz-Mindlin model the Young’s modulus determines both the simulated stiffness in compression and the initial slope of the shear force leading to an unresolvable contradiction. Instead, a different contact law was applied, a modification of the conical damage model (CDM), first introduced in [7]. In the normal contact an elastic regime exists, which is modelled with Hertz law.…”
Section: Dem Modelling Of Railway Ballastmentioning
confidence: 99%
See 2 more Smart Citations
“…This turned out to be impossible (at least for the used simple clump shape), as in the Hertz-Mindlin model the Young’s modulus determines both the simulated stiffness in compression and the initial slope of the shear force leading to an unresolvable contradiction. Instead, a different contact law was applied, a modification of the conical damage model (CDM), first introduced in [7]. In the normal contact an elastic regime exists, which is modelled with Hertz law.…”
Section: Dem Modelling Of Railway Ballastmentioning
confidence: 99%
“…In tangential direction, the classical Mindlin law together with a constant coefficient of friction can be used. If needed, the coefficient of friction can be adapted for every single contact to be stress dependent, as introduced in [18] or [7]. A detailed description of the CDM model equations and the used algorithm is given in [19].…”
Section: Dem Modelling Of Railway Ballastmentioning
confidence: 99%
See 1 more Smart Citation
“…Each research group independently devised a method for modelling the behaviour of scaled ballast with reference to the same laboratory data [27]. The work at Southampton, in a paper submitted for review [28] simultaneously with this one, proposed a new contact damage model as an alternative method for modelling the observed behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The Discrete Element Method (DEM) introduced by Cundall and Strack [18] has been used to study the mechanical behaviour of granular materials [19][20][21][22][23][24]. Chen et al [25] used DEM to simulate a box test of ballast reinforced with geogrid under confined and unconfined conditions and they reported that geogrid reinforcement can reduce ballast settlement when it is placed at an optimum location; and thus reduced the associated maintenance costs.…”
Section: Introductionmentioning
confidence: 99%